Occurrence and Population Dynamics of the Coffee Berry Borer (Hypothenemus hampei) on Coffee Plantations in Tanah Datar, Indonesia - Putri Tama, Duma (Universitas Andalas, 2025)
Coffee is an exported commodity that is important in earning foreign exchange. The coffee berry borer (Hypothenemus hampei) is the most crucial pest that has a detrimental effect on coffee growers in Indonesia. Research on the incidence of fruit borer on Arabica and Robusta coffee was carried out on smallholder plantations in the Tanah Datar district. The study aimed to determine the extent to which fruit borers infest Arabica and Robusta coffee, and to determine the populations of these pests so that they could be compared. Observation variables included planting conditions and cultivation methods, percentage of coffee plants infested, percentage of coffee cherries, insect identification in the laboratory, and coffee berry borer populations. The results showed that the average incidence of Hypothenemus hampei infestation on Arabica coffee plants in Tanah Datar district was 30.00% and 36.66% on Robusta coffee plants. The percentage of the egg stage in Arabica coffee is 37% and 27% in Robusta coffee. The percentage of the larval stage in Arabica coffee is 33%, and in Robusta coffee, it is 28%. Stadia Pupa on 20% Arabica coffee, 11% Robusta coffee. Stadia imago on Arabica coffee 54%, Robusta coffee 49%. This study provides important insights for integrated pest management strategies in Tanah Datar, particularly in optimizing pest control for Arabica and Robusta coffee.